2018
DOI: 10.1016/j.ygcen.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of energetic condition in wild baboons using fecal thyroid hormone determination

Abstract: Understanding how environmental and social factors affect reproduction through variation in energetic condition remains understudied in wild animals, in large part because accurately and repeatedly measuring energetic condition in the wild is a challenge. Thyroid hormones (THs), such as triiodothyronine (T3) and thyroxine (T4), have a key role in mitigating metabolic responses to energy intake and expenditure, and therefore are considered important biomarkers of an animal's energetic condition. Recent method d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 94 publications
2
25
1
Order By: Relevance
“…Although the underlying causes of reduced thyroid function in these foxes remains unknown, exposure to environmental toxins has been suggested (Munson 2010). Average fecal T3 concentrations measured in this study were higher than those reported for maned wolves (Vynne et al 2014) and several primate species (Schaebs et al 2016, Gesquiere et al 2018). Although these studies used different immunoassays and concentrations are not directly comparable, there is no indication that overall T3 concentrations of island foxes are abnormally low.…”
Section: Discussioncontrasting
confidence: 76%
“…Although the underlying causes of reduced thyroid function in these foxes remains unknown, exposure to environmental toxins has been suggested (Munson 2010). Average fecal T3 concentrations measured in this study were higher than those reported for maned wolves (Vynne et al 2014) and several primate species (Schaebs et al 2016, Gesquiere et al 2018). Although these studies used different immunoassays and concentrations are not directly comparable, there is no indication that overall T3 concentrations of island foxes are abnormally low.…”
Section: Discussioncontrasting
confidence: 76%
“…With regard to energy status in wild mammals, future studies could incorporate new physiological mediators [i.e. faecal Thyroid Hormone metabolites (THs); Gesquiere et al ., ], which would reinforce the understanding of the Biphasic Model that we have proposed. Guanacos present interesting features to evaluate the relationships between glucocorticoids and their response to energy demanding tasks.…”
Section: Discussionmentioning
confidence: 99%
“…It is common practice for scientists studying nonhuman primates in the wild to have teams that follow the animals on a daily basis and collect samples from known individuals. These methods allow collection of fecal samples that are regularly preserved and processed for laboratory analyses for hormonal, genetic, and disease studies [3234], and the methods can be modified to monitor ZIKV in study populations. Importantly, researchers will also now have a noninvasive way to check for ZIKV, particularly if reproductive issues are observed or if an infection is suspected.…”
Section: Discussionmentioning
confidence: 99%